2006
DOI: 10.1038/sj.onc.1209516
|View full text |Cite
|
Sign up to set email alerts
|

Combined treatment of colorectal tumours with agonistic TRAIL receptor antibodies HGS-ETR1 and HGS-ETR2 and radiotherapy: enhanced effects in vitro and dose-dependent growth delay in vivo

Abstract: We and others have demonstrated already that TRAIL (TNF-related apoptosis-inducing ligand) is a very promising candidate for molecular targeted anticancer therapy, especially when combined with ionizing radiation or other DNA-damaging agents. Agonist monoclonal antibodies that activate and are specific for the death signaling TRAIL receptors are an alternative method to stimulate the programmed cell death pathway. Phase 1 clinical trials have subsequently been conducted and shown a very good tolerability of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
69
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(76 citation statements)
references
References 52 publications
2
69
1
1
Order By: Relevance
“…As such, pharmacological inhibitors of the PI 3-K/Akt signaling pathway might achieve this aim: recent studies have demonstrated that agonistic mAbs against DR4 and DR5 can induce apoptosis in a variety of cultured and primary cancer cells (53). Other studies have shown that the combination of anti-human DR4 and DR5 mAbs with chemotherapeutic drugs or radiotherapy synergistically enhanced anti-tumor effects (54,55). Given the inherent difficulties of using wortmannin and LY294002 (stability, solubility and toxicity), efforts are underway to develop new PI 3-K pathway inhibitors; recently, a novel candidate has been reported that exhibits strong anti-tumor activity against human cancers without concomitant toxic effects on organs (56).…”
Section: Discussionmentioning
confidence: 99%
“…As such, pharmacological inhibitors of the PI 3-K/Akt signaling pathway might achieve this aim: recent studies have demonstrated that agonistic mAbs against DR4 and DR5 can induce apoptosis in a variety of cultured and primary cancer cells (53). Other studies have shown that the combination of anti-human DR4 and DR5 mAbs with chemotherapeutic drugs or radiotherapy synergistically enhanced anti-tumor effects (54,55). Given the inherent difficulties of using wortmannin and LY294002 (stability, solubility and toxicity), efforts are underway to develop new PI 3-K pathway inhibitors; recently, a novel candidate has been reported that exhibits strong anti-tumor activity against human cancers without concomitant toxic effects on organs (56).…”
Section: Discussionmentioning
confidence: 99%
“…Sensitivity to rTRAIL-induced apoptosis was reported in cell lines derived from human colon, lung, breast, kidney, brain and skin cancer (Ashkenazi et al, 1999). Till date, effective apoptosis induction by rTRAIL has been reported in human melanoma, leukemia, multiple myeloma, breast, bladder, prostate, renal or colon cancer in single treatments and/or combination therapy with chemotherapeutic agents (Chawla-Sarkar et al, 2002;An et al, 2003;Buchsbaum et al, 2003;van Geelen et al, 2003;VoelkelJohnson, 2003;Merchant et al, 2004;Georgakis et al, 2005;Kaufmann and Steensma, 2005;Kurbanov et al, 2005;Pukac et al, 2005;Bucur et al, 2006;Marini et al, 2006;O'Kane et al, 2006;Zeng et al, 2006). Thus, these cancers are the most promising indications for clinical trials of TRAIL and anti-DR5/DR4 mAb.…”
Section: Clinical Applicationmentioning
confidence: 99%
“…3,[7][8][9] In addition, TRAIL acts synergistically with chemotherapeutic drugs and can overcome drug resistance in tumor cell lines and animal models. [10][11][12] Immunohistochemical studies have demonstrated that the proapoptotic DR4 and DR5 are expressed in normal colon mucosa as well as colorectal adenomas and carcinomas, and their expression was increased in malignant versus normal cells. In comparison, there is a marked increase in sensitivity to TRAIL-induced apoptosis associated with progression from benign to malignant tumor with the assumption that sensitivity to TRAIL could be acquired early in colorectal tumorigenesis during the formation of adenoma.…”
mentioning
confidence: 99%